THE PRESENCE OF POSTURAL DEFORMITIES OF THE YOUTH DEPENDING ON THE LEVEL OF PARENTS KNOWLADGE ABOUT DEFICIENT BODY POSTURE - Zoran Bogdanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
The subject of this study is deterimining the presence of postural deformities in sagittal view (defi cient kyphotic and lordotic body posture) of the youth depanding on the level of parents knowladge about defi cient body posture. The complete content of the program was conducted in the territory of the city of Kragujevac in several elementary schools, comprising 299 students of the 5th grade and their parents. The object of this study was to determine the number of students with defi cient kyphotic and lordotic body posture, to determine the presence of dis arrangements depanding on the gender and to determine the presence of kyphotic and lordotic deformity depanding on the parents level of information about defi ciant body posture among children. Kyphotic deformity of the examiners of male population is mostly present in the group of parents who are poorly informed about body posture defi ciency. Regarding examiners of female population , the presence of deformation is equally divided on the group of parents who expressed themselves as being very well, those who are undecided and those who are poorly informed. The more signifi cant presence of kyphotic deformity is at examiners of male population than at the examiners of female population while the higher presence of lordotic deformity is at the examiners of female population. Regarding female population we can observe the highest presence of deformation in the group of parents who are undecided while the other groups are very equabal by the presence of deformation. Stated measures impose a statement that it is necessary to continuosly work on both - children education and parents education aiming to recognize posture defi ciency and physical deformation of school and preschool population and all of this with the object of reducing the deformation and on time detecting certain disarrangements and taking adaquate measures for its senctuary